2019
DOI: 10.1155/2019/5035871
|View full text |Cite
|
Sign up to set email alerts
|

Gender Differences in Eating Disorder Risk among NCAA Division I Cross Country and Track Student-Athletes

Abstract: Purpose. This study compared gender differences in eating disorder risk among NCAA Division I cross country and track distance running student-athletes. Methods. Six hundred thirty-eight male and female student-athletes competing at distances of 800m or greater completed the Eating Disorder Screen for Primary Care (ESP). Scores on the ESP were used as the risk of eating disorders. Results. Females screened positive at higher rates for risk of eating disorders than males on the ESP at a cutoff of 2 (sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…Similar results have been found in a sample of adolescent female and male athletes. In this case, the proportion was 1:3.5 amongst distance runners, with both males and females being at risk of ED, though with females exhibiting higher risk [36]. Similar results were found by Sundgot-Borgen & Torstveit (2004) [8] who reported that 20% of female athletes and 8% of male athletes met criteria for an ED, compared to 9% of female controls and 0.5% of male controls.…”
Section: Discussionsupporting
confidence: 86%
“…Similar results have been found in a sample of adolescent female and male athletes. In this case, the proportion was 1:3.5 amongst distance runners, with both males and females being at risk of ED, though with females exhibiting higher risk [36]. Similar results were found by Sundgot-Borgen & Torstveit (2004) [8] who reported that 20% of female athletes and 8% of male athletes met criteria for an ED, compared to 9% of female controls and 0.5% of male controls.…”
Section: Discussionsupporting
confidence: 86%
“…Notably, however, across all sport types the prevalence of male athletes identified as at-risk for an eating disorder and those with diagnosed eating disorders are lower than that observed in female athletes, 9% versus 21% and 8% versus 20%, respectively [35]. This pattern is supported by findings in male and female distance runners, where one report found that 46% of women were identified as at-risk for an eating disorder compared to only 14% of men [37]. It is interesting, however, that, although the prevalence of eating disorders in male athletes is lower than that of female athletes, it is similar to the prevalence of eating disorders in the general female population, suggesting that eating behaviors/eating disorders are an important concern in exercising men [35].…”
Section: Energy Availability Associated With An Initial Working Modelmentioning
confidence: 94%
“…Reports on collegiate athletes are mixed. Although female collegiate athletes have demonstrated a higher prevalence of EDs and ED symptomatology than male‐identified collegiate athletes (e.g., Krebs, Dennison, Kellar, & Lucas, 2019), it is less clear if the prevalence in collegiate athletes exceeds that of non‐athlete collegiate students (Greenleaf, Petrie, Carter, & Reel, 2009; Johnson, Powers, & Dick, 1999). Across ED behaviors, one of the only studies comparing college athletes, independent exercisers, and non‐exercisers observed greater severity of ED symptomatology at higher levels of sport participation (Holm‐Denoma, Scaringi, Gordon, Van Orden, & Joiner, 2009).…”
Section: Introductionmentioning
confidence: 99%